Caridean prawn (Crustacea, Decapoda) from Dong’ao Island, Guangdong, China - Chen, Qing-Hua; Chen, Wen-Jian; Guo, Zhao-Liang (Zootaxa, 2018)
The present study, based on a faunistic and ecological survey of caridean shrimps from Dong’ao Island, Guangdong Province, expands the knowledge of morphology, colouration, and distribution of three species, two of which belong to genus Caridina and one belong to genus Marcrobrachium. Caridina zhujiangensis, new species is distinguished from the closely related species C. typus H. Miline Edwars,1837 by shorter rostrum and with only one ventral margin teeth, the shape of the endopod of the first male pleopod and the appendix interna arising from distal 1/3 of endopod. Macrobrachium dongaoensis, new species, can be distinguished from its congeners M. inflatum Liang & Yan, 1985 by a combination of characters which includes short rostrum, the subequal male second pereiopods, the non–inflated palm, and the longer merus. A diagnosis of three speciesmore and full description of two new species are presented.